Growth and reproductive performance of the creole hen of green shell eggs of the Province of Chota, Cajamarca - Paredes A., Manuel (2019)
The aim of this study was to evaluate the productive and reproductive performance of the Creole egg hen of green shell eggs of the province of Chota, Cajamarca (Peru). Five hundred eggs were collected and artificially incubated to determine their hatchability. In the resulting chicks, the growth in confinement was evaluated for 16 weeks. Then, the birds were mated (5 females and 1 male) and the production and weight of eggs of six biotypes and the hatchability were determined under natural incubation. Significant differences (p<0.05) were found in the growth and size of the six biotypes evaluated. The birds initiated the oviposition between 17 and 19 weeks of age, with periods of posture of seven weeks interrupted by a broody period that could last up to three weeks. The hatchability was influenced by the conditions and types of incubation.